Nutritional value of Dasyphyllum diacanthoides (Less.) Carb.: an endemic tree used as suplementary forage in agroforestry systems (Bioagro, 2020)
In view of the evidence of the use of Dasyphyllum diacanthoides by peasants of the Region of the Araucanía, in the center-south zone of Chile, as winter food for their cattle, and the nonexistence of reports on the use of this forage, in this paper we determined the nutritional value of the species. Samples taken from different edible parts of D. diacanthoides were dried and subjected to a proximate analysis and detergent system to determine dry matter;  crude protein, ether extract; phosphorus, crude fiber, acid detergent fiber, neutral detergent fiber, total ash and metabolizable energy. It was shown that shoots and leaves are the edible parts that have the best nutritional values among the analyzed variables. Additionally, by calculating the digestible energy, digestible dry matter and the average metabolizable energy, it was found that D. diacanthoides has intermediate values for these variables compared to those of forage tree species used in different parts of the world and to the main local forage species. The plant presents balanced energy-protein ratio values, turning into an important winter supplement forage in view of the low availability of forage in the mountain localities of the Region of the Araucanía, as compared to other forage species used in Chile.
Keywords: Agroecology; cattle; local resources; rural communities; trevo